South African art history: the possibility of decolonising a discourse - Becker, Danielle Loraine (Centre for Film and Media Studies, 2018)
In light of recent calls to decolonise curricula at South African universities there has been a renewed interest in what decolonisation might specifically imply for particular academic disciplines. Art history in South Africa has long struggled to move away from its settler colonial origins towards a more Afrocentric focus and its art world has frequently been criticised for being elitist and dominated by white practitioners. To this end, one of the primary questions that this dissertation seeks to answer is to what extent indigenous, African art and African epistemology has been included in South African art history and the institutions that support despite the discourse's traces of colonialism. Through a discussion and analysis of South African art history this dissertation seeks to describe the changes in the discourse since the late twentieth-century in light of the entanglements of the national; the colonial and the decolonial. Such an analysis is provided through a discussion of the biases of art history as a discourse originating in Western Europe; the geographical location of museums and university departments; the character of South African art historical writing; the curatorial strategies used to display African art in South African museums and the specific nature of art history curricula as it is taught at South African universities. The dissertation that follows therefore aims to provide an overarching view of South African art history that takes into account a range of factors impacting its particular framing so that the question of decolonisation can be adequately addressed. The dissertation finds that South African art history has a specific, settler colonial character and that historical African art has been neglected in art historical discourse despite overt attempts to transform the nature of the discipline post-democracy. It is argued that this may be the result of a shift in focus towards contemporary practice in the twenty-first century and away from the historical as a result of a resistance to cultural or racial labels attributed to art due to the legacy of apartheid legislation. As such, I argue that South African art history may find a path towards decolonisation through a renewed focus on historical South African and African art that is perceived on its own terms.